2017
DOI: 10.7575/aiac.ijels.v.5n.2p.67
|View full text |Cite
|
Sign up to set email alerts
|

Teachers and Learners’ Perceptions of Applying Translation as a Method, Strategy, or Technique in an Iranian EFL Setting

Abstract: It has been found that translation is an efficient means to teach/learn grammar, syntax, and lexis of a foreign language. Meanwhile, translation is good for beginners who do not still enjoy the critical level of proficiency in their target language for expression.  This study was conducted to examine the teachers and learners’ perceptions of employing translation in the foreign language classroom; i.e., the effects, merits, demerits, limitations, as well as its use as a method, strategy or technique. Both quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 0 publications
1
11
1
Order By: Relevance
“…Furthermore, the questionnaire in this study included one item from Oxford's (1990) translation strategies category, "Write the meaning of new words in your native language", which is not included in Schmitt's VLSQ taxonomy. The translation is viewed as an efficient way to teach/learn grammar, syntax, and lexis of a foreign language (Mollaei, Taghinezhad, & Sadighi, 2017). Reliability of this questionnaire was calculated using Cronbach's Alpha and turned out to be 0.92 which is an acceptable number.…”
Section: Instrumentationmentioning
confidence: 99%
“…Furthermore, the questionnaire in this study included one item from Oxford's (1990) translation strategies category, "Write the meaning of new words in your native language", which is not included in Schmitt's VLSQ taxonomy. The translation is viewed as an efficient way to teach/learn grammar, syntax, and lexis of a foreign language (Mollaei, Taghinezhad, & Sadighi, 2017). Reliability of this questionnaire was calculated using Cronbach's Alpha and turned out to be 0.92 which is an acceptable number.…”
Section: Instrumentationmentioning
confidence: 99%
“…Furthermore, the study of perception and cognition has become mushrooming issue in English Foreign Language (EFL) research in recent years as reported by Borg, (2003), Pham & Malvetti (2012), Dja'far, Cahyono, & Bashtomi (2016), Othman & Kiely (2016), and Mollaei, Taghinezhad, & Sadighi (2017). Then, the exploration of how ESP teachers become language teachers, what perception they have as English teachers, how they implement it in the teaching practices, and what factors affect their perception are common issues revealed.…”
Section: Amentioning
confidence: 99%
“…Researches on the use of deductive and inductive approaches of teaching grammar have been conducted in various contexts [1]- [2]- [3], however within the Afghan context, to the knowledge of the researchers, there is a lack of research. In fact, it can be stated that while there have been lots of research on ELT globally, not much has been investigated about the teaching and learning of English Language in Afghanistan.…”
Section: Introductionmentioning
confidence: 99%